Optimising health and safety of people who inject drugs during transition from acute to outpatient care: narrative review with clinical checklist. Issue 1088 (22nd March 2016) - Thakarar, Kinna; Weinstein, Zoe M; Walley, Alexander Y
Abstract: The opioid epidemic in the USA continues to worsen. Medical providers are faced with the challenge of addressing complications from opioid use disorders and associated injection drug use. Unsafe injection practices among people who inject drugs (PWID) can lead to several complications requiring acute care encounters in the emergency department and inpatient hospital. Our objective is to provide a narrative review to help medical providers recognise and address key health issues in PWID, who are being released from the emergency department and inpatient hospital. In the midst of rises in overdose deaths and infections such as hepatitis C, we highlight several health issues for PWID, including overdose and infection prevention. We provide a clinical checklist of actions to help guide providers in the care of these complex patients. The clinical checklist includes strategies also applicable to low-resource settings, which may lack addiction treatment options. Our review and clinical checklist highlight key aspects of optimising the health and safety of PWID.